2006
DOI: 10.1113/expphysiol.2006.033506
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensing by mitochondria at complex III: the paradox of increased reactive oxygen species during hypoxia

Abstract: All eukaryotic cells utilize oxidative phosphorylation to maintain their high-energy phosphate stores. Mitochondrial oxygen consumption is required for ATP generation, and cell survival is threatened when cells are deprived of O 2 . Consequently, all cells have the ability to sense O 2 , and to activate adaptive processes that will enhance the likelihood of survival in anticipation that oxygen availability might become limiting. Mitochondria have long been considered a likely site of oxygen sensing, and we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
584
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(611 citation statements)
references
References 92 publications
22
584
2
3
Order By: Relevance
“…4, A-C). Experimental data has also revealed that the NADPH oxidase (58,59) and mitochondrial electron transport complexes I and III are major cellular sources of ROS, principally in the form of the superoxide anion and hydrogen peroxide (14,37,60). Our observations concur with this data because inhibition of the aforesaid ROS sources abrogated the CD36 hypoxic signal (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…4, A-C). Experimental data has also revealed that the NADPH oxidase (58,59) and mitochondrial electron transport complexes I and III are major cellular sources of ROS, principally in the form of the superoxide anion and hydrogen peroxide (14,37,60). Our observations concur with this data because inhibition of the aforesaid ROS sources abrogated the CD36 hypoxic signal (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…105,106 The primary site of hypoxiadriven ROS production is believed to be complex III of the mitochondrial respiratory chain, where a quasi-stable ubisemiquinone radical is repeatedly generated during the electron transport process. 106,107 Molecular oxygen can capture the electron from this ubisemiquinone, yielding superoxide which can form hydrogen peroxide. Both ROS can reach the cytosol; superoxide via voltage dependent anion channels, while the noncharged H 2 O 2 can simply diffuse through the outer mitochondrial membrane.…”
Section: Autophagy Ros and Cancer: A Two-faced Storymentioning
confidence: 99%
“…61,106,107 HIFs are master players in the adaptive response to hypoxia and influence the transcription of hundreds of genes, including the BH3-only proteins BNIP3 and BNIP3L. Thus, under hypoxia, HIF-1-mediated induction of these BH3-only proteins can free Beclin 1 from Bcl-2/Bcl-X L , thereby stimulating autophagy.…”
Section: Autophagy Ros and Cancer: A Two-faced Storymentioning
confidence: 99%
“…The thiol groups are reduced at normal conditions but upon oxidation, a disulfide bond is formed that changes the conformation of the hinge domain and separates the YFP and CFP. This decreases the energy transfer from CFP to YFP enhancing the CFP signal while decreasing the YFP signal during oxidation [63]. Such a probe can be overexpressed in cells and the ratio of CFP to YFP fluorescence taken as a measure of cellular ROS levels in real time, a readout independent of probe concentration.…”
Section: Measurement Of Cellular Rosmentioning
confidence: 99%